Prediction of Location of Infarct-related Artery in acute Myocardial Infarction from Surface Electrocardiogram, its Clinical Importance and Therapeutic Strategy: A Review - Haque, Mostashirul; Alam, Md Shafiul; Ahmed, Sabbir Jashim; Khatun, Sufia; Urmi, Nusrat Jahan; Joarder, Ariful Islam; Amin, Md Rasul; Islam, Lohani Md Tajul; Hasan, Md Nazmul (University Heart Journal, 2015)
Abstract not available University Heart Journal Vol. 10, No. 2, July 2014; 85-87